Investigating role of ASIC2 in synaptic and behavioral responses to drugs of abuse - Fuller, Margaret J.; Gupta, Subhash C.; Fan, Rong; Taugher-Hebl, Rebecca J.; Wang, Grace Z.; Andrys, Noah R. R.; Bera, Amal K.; Radley, Jason J.; Wemmie, John A. (Frontiers in Molecular Biosciences, 2023)
Drugs of abuse produce rearrangements at glutamatergic synapses thought to contribute to drug-reinforced behaviors. Acid-Sensing Ion Channels (ASICs) have been suggested to oppose these effects, largely due to observations in mice lacking the ASIC1A subunit. However, the ASIC2A and ASIC2B subunits are known to interact with ASIC1A, and their potential roles in drugs of abuse have not yet been investigated. Therefore, we tested the effects of disrupting ASIC2 subunits in mice exposed to drugs of abuse. We found conditioned place preference (CPP) to both cocaine and morphine were increased in Asic2-/- mice, which is similar to what was observed in Asic1a-/- mice. Because nucleus accumbens core (NAcc) is an important site of ASIC1A action, we examined expression of ASIC2 subunits there. By western blot ASIC2A was readily detected in wild-type mice, while ASIC2B was not, suggesting ASIC2A is the predominant subunit in NAcc. An adeno-associated virus vector (AAV) was used to drive recombinant ASIC2A expression in NAcc of Asic2-/- mice, resulting in near normal protein levels. Moreover, recombinant ASIC2A integrated with endogenous ASIC1A subunits to form functional channels in medium spiny neurons (MSNs). However, unlike ASIC1A, region-restricted restoration of ASIC2A in NAcc was not sufficient to affect cocaine or morphine CPP, suggesting effects of ASIC2 differ from those of ASIC1A. Supporting this contrast, we found that AMPA receptor subunit composition and the ratio of AMPA receptor-mediated current to NMDA receptor-mediated current (AMPAR/NMDAR) were normal in Asic2-/- mice and responded to cocaine withdrawal similarly to wild-type animals. However, disruption of ASIC2 significantly altered dendritic spine morphology, and these effects differed from those reported previously in mice lacking ASIC1A. We conclude that ASIC2 plays an important role in drug-reinforced behavior, and that its mechanisms of action may differ from ASIC1A.